2017
DOI: 10.1186/s13018-017-0560-9
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in extreme sports

Abstract: Extreme sports (ES) are usually pursued in remote locations with little or no access to medical care with the athlete competing against oneself or the forces of nature. They involve high speed, height, real or perceived danger, a high level of physical exertion, spectacular stunts, and heightened risk element or death.Popularity for such sports has increased exponentially over the past two decades with dedicated TV channels, Internet sites, high-rating competitions, and high-profile sponsors drawing more parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Participation in adventure tourism is usually associated with a risk of injury or even death (Laver et al, 2017). Over 4 million injuries in adventure sports were reported between year 2000 to 2011 (Sharma et al, 2015).…”
Section: Injury and Incidents In Adventure Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in adventure tourism is usually associated with a risk of injury or even death (Laver et al, 2017). Over 4 million injuries in adventure sports were reported between year 2000 to 2011 (Sharma et al, 2015).…”
Section: Injury and Incidents In Adventure Tourismmentioning
confidence: 99%
“…Over 4 million injuries in adventure sports were reported between year 2000 to 2011 (Sharma et al, 2015). Recent data from Laver et al (2017), suggested that the risk and severity of injury in global adventure tourism was unexpectedly high with approximately 70% of the total injury rate was recorded. Meanwhile in Malaysia, Zakaria et al (2017) and Majeedkutty et al (2017) documented that 85.7% and 83.8% respectively experienced injuries during adventure activities in their report.…”
Section: Injury and Incidents In Adventure Tourismmentioning
confidence: 99%
“…Injuries occur in extreme sports as well and become important stressors. According to Laver, Pengas and Mei-Dan (2017), higher injury rates are noted in new and inexperienced athletes who have just engaged in extreme sports. Competitions involve pressure and certain demands that increase the likelihood of injury.…”
Section: Extreme Sports and Injuriesmentioning
confidence: 99%
“…The unusual and sometimes risky physical and cognitive demands of AES may create conditions under which potential risk factors can more readily exert their influence. Recent research suggests that the risk and severity of injury in some AES may be high (Heggie & Caine, 2012;Laver, Pengas, & Mei-Dan, 2017). For example, researchers reviewed 2000-2011 National Electronic Injury Surveillance System data for seven popular extreme sports featured at the Winter and Summer X Games: surfing, mountain biking, motocross, skateboarding, snowboarding, snowmobiling and snow skiing (Sharma et al, 2015).…”
Section: Balancing Risks and Benefitsmentioning
confidence: 99%